Penentuan Solusi Optimal Kinerja Guru dengan Menggunakan Analisis SITOREM - Rahmawati Rahmawati; Bibin Rubini; Lina Novita (SAP (Susunan Artikel Pendidikan), 2025)
The purpose of this study is to determine the optimal solution for variables that support teacher performance based on an analysis of indicators for each research variable. The method used is quantitative, employing the SITOREM (Scientific Identification Theory to Conduct Operation Research in Education Management) analysis technique. Based on the analysis results, it can be concluded that there are 9 indicators with scores above 4.00 and 16 indicators below 4.00. Therefore, it can be concluded from this study that there are 16 indicators that need to be improved, namely 1) Time Management, 2) Technology Utilisation, 3) Work Quality Achievement, 4) Knowledge Improvement, 5) Knowledge Evaluation, 6) Knowledge Distribution, 7) Ability to Understand Others, 8) Providing views, ideas, and concepts for organisational progress, 9) Collaboration, 10) Togetherness, 11) Mutual Trust, 12) Concern, 13) Working Conditions, 14) Salary/Income, 15) Promotion Opportunities, 16) Supervision. The implication of this study is that schools, in this case school leaders, can make decisions to improve weak indicators according to the SITOREM results in order to improve educational management in schools.